Elemento de volume representativo do concreto: uma contribuição no aspecto geométrico com a utilização de elipsoides como inclusões - SILVA, Davi Barbosa Costa da (2020)
The social and economic importance of great ventures, as the hydroelectrics, justifies the adoption of the largest possible number of security measures. In the case of structures, particularly in dams made of concrete, it verifies the use of instruments of precision to keep up with the behavior of the massif and the visual inspections. These two approaches complement each other and are extremely useful in the adoption of parameters that guide the maintenance measures. In order to add and to optimize these techniques and methods, it may be adopted computational models that allow the forecast of the concrete structures behavior. Between the possible approaches, it mentions the multiscale analysis, in which one searches to relate parameters of the micro to the meso and the macrostructure. It observes the existence of algorithms that search to enable these improvements, generating, therefore, possibility of innovation. In order to contribute in the area, in this paper it searches to improve and to develop one of the tools adopted in this branch. By the use of the notions of representative volume element (RVE) and focusing on the geometric aspects of the matter, it was elaborated a sequence of instructions that allows the random generation of ellipsoidal inclusions, representing the coarse aggregates of the concrete surrounded by the interfacial transition zone, applying geometrical adjusts to the quadrics that are located in the proximities of the faces of the RVE, basing it on the take-and-place method and on related researches. The result was an algorithm that provides an organized data structure so that it can be used as parameter of input in proper applications to multiscale analysis.